A Rare Case of Gastric Ectopic Pancreatic Tissue - An Incidental finding - Shah, Rajat Kumar; Singh, Mrinalini; Dhanuk, Dipesh Mandal (Birat Journal of Health Sciences, 2023)
Ectopic pancreas is an infrequent lesion presenting as a nodule or a submucosal mass in the gastrointestinal tract. Depending upon its anatomical location, it can cause clinical symptoms like abdominal pain, intussusceptions, or obstruction, or it can remain clinically silent. Though radiologic diagnostic tools are available, the preoperative diagnosis is tough and is seldom made. We report a case of a 61-year-old male with the chief complaint of pain in the abdomen for 15 days. Advanced diagnostic tools like Contrast enhanced CT scan can characterise the submucosal mass in the stomach and able to confirm the nature of the lesion, whether it was non-neoplastic, benign, or malignant. Therefore, surgical excision was done. The final confirmatory diagnosis of ectopic pancreas in the stomach was made on histopathologic examination.